The Significance of the National Architectural Style in the Development of Design-Code Rules for the Historical Centers of the City of Bukhara (Journal of Architectural Design, 2022)
In the development of the design-code of the historical regions of Bukhara, the analysis of the architectural style of the city and the national elements of the building facades are discussed. The state of the hotel business and its construction processes, the processes of combining national style and modernity in hotels, and the formation of the new "Bukhara style" are discussed. In addition, there is information about the research to identify local materials in the development of city design code rules